Determinants of Turnover in Maritime Workforces: Competence, Career Path, and Engagement with Job Satisfaction Mediation - Usmar Usmar; Tamrin Lanopi; Bahtiar Bahtiar; Yoyon Supriadi; Sugeng Suroso; Zahara Tussoleha Rony; I Dewa Ketut Kerta Widana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee turnover remains a critical challenge in the maritime transportation sector, where unique working conditions such as long-term separation from family, high occupational risks, and irregular schedules often lead to dissatisfaction and high resignation rates. This study aims to analyze the determinants of employee turnover by conducting a systematic literature review of previous studies on employee competence, career path, and work engagement, with job satisfaction as a mediating variable. Articles were collected from reputable databases including Scopus, Web of Science, Emerald, Springer, Sage, Thomson Reuters, and Sinta journals, covering publications from 2016 to 2024. Through a structured screening process, 32 relevant articles were identified and analyzed using comparative analysis to synthesize similarities, differences, and gaps across studies. The findings reveal that employee competence, career path, and work engagement significantly affect turnover, both directly and indirectly through job satisfaction. However, research focusing specifically on the maritime sector remains limited, creating a contextual gap in understanding turnover under extreme occupational settings. The proposed conceptual framework integrates these variables to provide a holistic model of turnover dynamics, offering theoretical enrichment and practical guidance for human resource strategies. This study contributes to the literature by highlighting the unique context of maritime transportation and by formulating hypotheses for future empirical validation. Keywords: Employee Turnover, Job Satisfaction, Employee Competence, Career Path, Work Engagement